2013
DOI: 10.4322/rca.2013.034
|View full text |Cite
|
Sign up to set email alerts
|

Management and cost of urea application in maize grown in northern Paraná state, Brazil

Abstract: Urea is the most widely used nitrogen fertilizer in maize. In this study, we aimed to evaluate the agronomic performance of maize under different rates and forms of N application and to identify the economic efficiency provided by this crop in relation to this type of fertilizer. To this end, we conducted a field experiment in a Eutroferric Dark Red Latosol (Oxisol) using the maize cultivar AG 8021. Nine treatments were tested comprising the application of 40, 80, 120, 160, 200, and 240 kg ha -¹ of N (urea) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
3
0
3
Order By: Relevance
“…The time of N application significantly did not differ as to crop yield (Table 2) indicating that the N fertilization can be done on the sowing time or side dressing in the maize under NTS. Silva et al (2005b), Santos et al (2010) and Pissinati et al (2013) also did not find significant differences in maize crop yield when they compared the sowing application or side dressing; however, Silva et al (2005a) reported higher grain yield (GY) when the half rate was applied in the sowing and the rest in topdressing (from 4 to 6 or 8 to 10 leaves) or the whole N was topdressing applied (from 4 to 6 leaves).…”
Section: Crop Yieldmentioning
confidence: 90%
“…The time of N application significantly did not differ as to crop yield (Table 2) indicating that the N fertilization can be done on the sowing time or side dressing in the maize under NTS. Silva et al (2005b), Santos et al (2010) and Pissinati et al (2013) also did not find significant differences in maize crop yield when they compared the sowing application or side dressing; however, Silva et al (2005a) reported higher grain yield (GY) when the half rate was applied in the sowing and the rest in topdressing (from 4 to 6 or 8 to 10 leaves) or the whole N was topdressing applied (from 4 to 6 leaves).…”
Section: Crop Yieldmentioning
confidence: 90%
“…Neste estudo, optou-se por não utilizar os preços referentes ao mês de outubro de 2008 devido à alta no valor dos fertilizantes no ano de 2008 (US$ 416,40 e US$ 665,63) por tonelada SA e ureia, respectivamente, em relação aos anos anteriores. O efeito benéfico do N na produtividade do milho é amplamente relatado na literatura (Silva et al, 2005b;Veloso et al, 2006;Fidelis et al, 2007;Duete et al, 2009;Souza et al, 2011;Pissinati et al, 2013), porém é preciso ressaltar a importância da avaliação econômica, visto que a análise dos custos de utilização da adubação nitrogenada demonstra se o incremento na produtividade de grãos pode ser ou não economicamente satisfatório. Silva et al (2005a) ressaltaram que as diferenças nas quantidades de N a serem utilizadas na adubação, dependem, além da produtividade, do nível do elemento no solo, o que está relacionado ao histórico de uso da área, o preço de mercado do milho e o custo do fertilizante nitrogenado.…”
Section: Methodsunclassified
“…Diversos trabalhos têm sido realizados no intuito de estudar doses de N e a eficiência do uso de fertilizantes nitrogenados, inclusive com inibidores de nitrificação (Fernandes et al, 2005;Souza et al 2011;Pissinati et al, 2013;Andrade et al, 2014), no entanto, são poucos os estudos que determinam a sua viabilidade econômica. Portanto, testa-se a hipótese de que, embora o uso de fertilizantes nitrogenados seja eficiente e aumente a produtividade do milho, nem sempre esse acréscimo é suficiente para cobrir os custos e proporcionar lucratividade.…”
Section: Abstract: Nitrogen (N) Is the Most Required Nutrient To Cornunclassified
“…Dessa forma, o uso de tecnologias que proporcionem uma maior tolerância das plantas ao estresse salino desempenha um importante papel em manter a produção global de alimentos no futuro, visto ser o milho um dos mais importantes produtos para alimentação humana e animal (Pissinati et al, 2013). Dentre as tecnologias mais promissoras para atuarem na fase inicial de desenvolvimento, em condições de estresse, está a utilização de substâncias com efeito de reguladores de crescimento (Veluppillai et al, 2009).…”
Section: Introductionunclassified